2020
DOI: 10.1038/s41467-020-16758-9
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil function in adipose tissue is regulated by Krüppel-like factor 3 (KLF3)

Abstract: The conversion of white adipocytes to thermogenic beige adipocytes represents a potential mechanism to treat obesity and related metabolic disorders. However, the mechanisms involved in converting white to beige adipose tissue remain incompletely understood. Here we show profound beiging in a genetic mouse model lacking the transcriptional repressor Krüppel-like factor 3 (KLF3). Bone marrow transplants from these animals confer the beige phenotype on wild type recipients. Analysis of the cellular and molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 69 publications
(92 reference statements)
2
33
0
Order By: Relevance
“…However, macrophages within the adipose-resident compartment actually decline with age, and the proportion of pro-inflammatory macrophages increases (2,15), suggesting that despite cytokine mRNA expression, old ILC2 function is impaired and this could further compound their numerical loss. Notably, this premise of functionality versus numbers was recently demonstrated in adipose tissue eosinophils (40). We also noted enhanced expression of Ifngr1, Ifnar1, and Ifnar2 in aged ILC2 (Fig.…”
supporting
confidence: 82%
“…However, macrophages within the adipose-resident compartment actually decline with age, and the proportion of pro-inflammatory macrophages increases (2,15), suggesting that despite cytokine mRNA expression, old ILC2 function is impaired and this could further compound their numerical loss. Notably, this premise of functionality versus numbers was recently demonstrated in adipose tissue eosinophils (40). We also noted enhanced expression of Ifngr1, Ifnar1, and Ifnar2 in aged ILC2 (Fig.…”
supporting
confidence: 82%
“…In addition to ILC2-derived IL-33-dependent eosinophils recruitment to AT, IL-33 was also shown to recruit eosinophils in the absence of ILC2s ( 178 ). It was recently demonstrated that the transcriptional repressor krüppel-like factor 3 (KLF3)-deficient mice exhibited profound WAT beiging, which was accompanied by an accumulation of AT eosinophils ( 511 ).…”
Section: The Adipose Immune System As O Regulator Of Adaptive Thermogmentioning
confidence: 99%
“…47 Additionally, eosinophils can activate beige fat cells by secreting certain factors such as KLF3, thereby reducing obesity-related disease. 48 Neutrophils are often the first immune cells to reach the site of inflamed tissue. The production of leukotriene B 4 (LTB 4) in AT promotes the accumulation of neutrophils which express IL-1β through the NF-κB pathway to cause chronic inflammation.…”
Section: Immune Cells In Obese Adipose Tissue Inflammationmentioning
confidence: 99%